: Pandangan Muhammadiyah Dan Hukum Positif Indonesia - Yulizain Putra; Firdaus; Rahmat Hidayat (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2025)
This study examines the family resilience challenges posed by repeated informal marriages (nikah siri) using the case of Vicky Prasetyo as a focal example. The research aims to explore the perspectives of Muhammadiyah and Indonesian positive law regarding these challenges. The method employed is a qualitative content analysis of normative texts to identify the main challenges and responses related to family sustainability within the context of repeated nikah siri. The results reveal significant legal, social, and religious tensions that complicate the protection and welfare of families involved. Muhammadiyah emphasizes the importance of lawful marriage procedures to safeguard family stability, while Indonesian positive law categorically regulates marriage legality but faces enforcement limitations especially in informal marriage cases. The discussion highlights the gap between religious-social norms and statutory law, urging integrated efforts to address family vulnerabilities due to repeated nikah siri. This study contributes to a deeper understanding of legal-religious dynamics influencing family resilience in Indonesia.